THE EFFECT OF CLASSICAL MUSIC THERAPY ON THE RISK OF VIOLENT BEHAVIOR IN RPK PATIENTS AT DR. ARIF ZAINUDIN RSJD - Adibatul Istiqomah; Didik Iman Margatot; Annisa Cinta Kalista; Meinisa Putri Prasetyo; Nia Meilani; Wahyu Putri Lestari (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Background: Risk of Violent Behavior (RVB) is a common mental health nursing problem among patients with severe mental disorders and may endanger both patients and others. One non-pharmacological intervention to reduce RVB is Group Activity Therapy using classical music. Objective: This study aimed to analyze the effect of classical music group activity therapy on the risk of violent behavior in RVB patients. Methods: This study employed a pre-experimental design with a one group pretest–posttest approach. The subjects consisted of four RVB patients hospitalized in the Gatotkaca Ward of RSJD dr. Arif Zainuddin, Central Java Province. The intervention involved playing instrumental classical music with a slow tempo for approximately 10–20 minutes. The risk of violent behavior was measured before and after the intervention using the RUFA instrument through behavioral observation. Results: The results showed behavioral improvements in all patients, indicated by enhanced emotional control, reduced agitation, and increased social interaction. Three patients showed improvement in RUFA category, while one patient demonstrated an increased score within the same category. Conclusion: Classical music group activity therapy is effective in reducing the risk of violent behavior and can be recommended as a complementary intervention in mental health nursing care.